The β20–β21 of gp120 is a regulatory switch for HIV-1 Env conformational transitions - Alon Herschhorn (Nature Portfolio, 2017)
Binding of viral envelope glycoproteins (Env) to the host cell CD4 receptor mediates HIV-1 entry. Here, the authors develop compounds that inhibit the CD4-induced conformational changes in Env and show that the gp120 β20-β21 element is a key regulator for Env transitions.